Toward Shuttle‐Free Zn–I2 Battery: Anchoring and Catalyzing Iodine Conversion by High‐Density P‐Doping Sites in Carbon Host - Peng‐Fang Zhang; Jia‐Hui Li; Shao‐Jian Zhang; Da‐Cheng Li; Su‐Yuan Zeng; Shu‐Ling Xu; Qing‐Xia Yao; Ling‐Yang Liu; Ding, Lei; Heng‐Xiang Li; Yi‐Yang Hu; Jun‐Tao Li; et al. (Advanced functional materials, 2024)
Zn–iodine (I2) battery, as a promising energy storage device, especially under high I2 loading, is harassed by the shuttle effect of the soluble polyiodide intermediates. Herein, the bifunctional role of 2D carbon nanosponge with rich P‐dopant (4.2 at%) and large specific surface area (1966 m2 g−1) in anchoring I2/Ix− (x = 1, 3 or 5) and catalyzing their mutual conversion is reported. Both experiment and computational results reveal the transfer of electrons from the P‐doped site to iodine species, showing strong interfacial interaction. When being used as a host, it possesses high specific capture capacity for I2 (3.34 giodine g−1 or 1.6 mgiodine m−2) and Ix− (6.12 gtriiodide g−1 or 3.1 mgtriiodide m−2), which thus effectively suppresses the shuttle effect, supported by in situ UV–vis and Raman spectra. In addition to the strong interfacial interaction that favors iodine conversion, the P‐doped sites can also catalyze the conversion of I5− to I2, which is the rate‐determining step. Consequently, Zn–I2 batteries under a high I2 content (70 wt%) deliver high specific capacity (220.3 mAh g−1), superior Coulombic efficiency (>99%), and low self‐discharge rate; moreover, they can also operate steadily at 2 A g−1 with ignorable capacity decay for 10 000 cycles.